Cumulative effects of transcranial direct current stimulation on EEG oscillations and attention/working memory during subacute neurorehabilitation of traumatic brain injury. Issue 3 (March 2015) - Ulam, F.; Shelton, C.; Richards, L.; Davis, L.; Hunter, B.; Fregni, F.; Higgins, K.
Highlights Immediate and cumulative increases in cortical excitability were seen among patients with traumatic brain injuries in response to anodal tDCS to the left dorsolateral prefrontal cortex. Following 10 consecutive sessions, decreased delta and increased alpha were noted, which extended beyond the region of the anodal electrode, suggesting improved regulation of cortical excitability. Study results suggest EEG may provide a useful biological marker for selection of patients likely to benefit from tDCS.